Demonstration of B-1,3-glucanase activities in lutoids of Hevea brasiliensis latex - Breton F; Coupe M; DAuzac J; Sanier C (Journal of Natural Rubber Research, 1995)
B-1,3-glucanase activity, generally known to be involved in plant defence reactions against pathogens, was observed in extracts of lutoids from Hevea latex. The B-1,3-glucanase activities detected after native isoelectrofocusing (IEF) led to the visualisation of five bands consisting of three basic isozymes (pI 10.00 +_ 0.24 and 9.0 +_ 0.22), and two acid isozymes (pI 5.49 +_ 0.02 and 4.88 +_ 0.03). Immunodetection with tobacco polyclonal antibodies against acid and basic B-1,3-glucanases, revealed the same protein profile, characterised by three major bands with molecular weights of 38.9 +_ 1.2, 36.4 +_ 0.89 and 30.1 +_ 1 kD, respectively. The presence of apparently constitutive chitinases and B-1,3-glucanases in lutoids is discussed.
Keywords: B-1,3-glucanase; Hevea brasiliensis; Latex; Lutoids